2005
DOI: 10.1136/jnnp.2003.033662
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular lymphoma: magnetic resonance imaging correlates of disease dynamics within the central nervous system

Abstract: Background: Intravascular lymphoma (IVL) is a rare non-Hodgkin's lymphoma with relative predilection for the central nervous system. In the absence of extraneural manifestations, the disease is not recognised until autopsy in the majority of cases underlining the need for new clinical markers. Methods: This is a retrospective series of five patients with IVL seen at a single institution over three years. An advanced magnetic resonance imaging (MRI) protocol was performed at various time points prior to diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 15 publications
(6 reference statements)
1
60
0
Order By: Relevance
“…Among the involved organs, it has been demonstrated that IVL has a predilection for CNS involvement at either presentation or relapse; however, neurologic manifestations of IVL are extremely heterogeneous and can include sensory and motor deficits as well as altered consciousness. Neuroimaging findings vary widely and range from the diffuse involvement of the deep white matter to infarctlike lesions, 23 reflecting the heterogeneity of CNS involvement in terms of true lymphoma infiltration and vascular occlusion. In addition, many patients with IVL have a deteriorated performance status at diagnosis, and the diagnosis of CNS involvement often may be made by observing symptoms alone.…”
Section: Discussionmentioning
confidence: 99%
“…Among the involved organs, it has been demonstrated that IVL has a predilection for CNS involvement at either presentation or relapse; however, neurologic manifestations of IVL are extremely heterogeneous and can include sensory and motor deficits as well as altered consciousness. Neuroimaging findings vary widely and range from the diffuse involvement of the deep white matter to infarctlike lesions, 23 reflecting the heterogeneity of CNS involvement in terms of true lymphoma infiltration and vascular occlusion. In addition, many patients with IVL have a deteriorated performance status at diagnosis, and the diagnosis of CNS involvement often may be made by observing symptoms alone.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are similar to changes consistent with CNS vasculitis, are at least partially reversible, and correlate to some degree with disease course and response to chemotherapy. 18 …”
Section: Pathologic Featuresmentioning
confidence: 99%
“…[1,2,5] Neuroimaging findings are non-specific and imaging abnormalities are detected in about half of patient with IVLBCL who present with neurologic symptoms. [5,6] CT is generally non-diagnostic, though MRI can show non-specific hyperintensity of white-matter lesions suggestive of small-vessel ischemic disease or demyelination. [1,5,6] Given that IVLBCL typically presents as a disseminated disease, no standard procedure for organ biopsy has been established for this disease.…”
Section: Discussionmentioning
confidence: 99%